Komparasi Sistem Hukum Dalam Peradilan : Studi Kasus Hukum Indonesia Dan Hukum Malaysia - Syifa Lailia; Sri Hadiningrum (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Indonesia's legal system continues to be predominantly influenced by modern laws introduced by European countries, creating a distinctive character within the Indonesian legal framework. The familial nature of Indonesia's legal system tends to prioritize form over substance, paying less attention to moral aspects. This raises issues related to the imbalance of humanitarian values within the legal system. Despite its status as an independent and sovereign nation, Indonesia still grapples with cases of dishonesty and ethical violations in law enforcement. Therefore, this research aims to compare the judicial systems of Indonesia and Malaysia using a normative legal research method. The comparison reveals the complexity and uniqueness of legal development in both countries. Indonesia, inheriting Dutch civil law, has a court structure that separates general, religious, administrative, and military jurisdictions. In contrast, Malaysia, blending English law with Islamic and customary law, demonstrates strong diversification in court forms and jurisdictions. These differences reflect legal adaptations to history, culture, and the needs of local communities. While both systems have strengths and weaknesses, there is room for improvement in terms of dispute resolution efficiency and jurisdictional clarity.